2018
DOI: 10.3389/fped.2018.00138
|View full text |Cite
|
Sign up to set email alerts
|

The Preschool Physical Literacy Assessment Tool: Testing a New Physical Literacy Tool for the Early Years

Abstract: Background: Physical literacy is essential to physical activity across the lifespan. While there is an emerging body of research on physical literacy in school-aged children, the preschool years have largely been ignored. We tested the psychometric properties of the new tool, the Preschool Physical Literacy Assessment Tool (Pre-PLAy) designed to address this gap.Methods: We recruted 78 children (aged 19–49 months) across 5 childcare centers in Hamilton, Ontario. Two Early Childhood Educators (ECE) completed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 18 publications
0
20
1
2
Order By: Relevance
“…The PLAY Tools (PLAYfun, PLAYparent, and PLAYself) have evidence of internal consistency (33), and PLAYself has acceptable test–retest reliability (30). There is initial evidence for the Pre-PLAY tool to assess physical literacy among preschool-aged children, but poor reliability among boys indicates a continued need for improvements (34). Among adults, previous studies have used the CAPL, PPLI, or composite measures to assess physical literacy.…”
Section: Discussionmentioning
confidence: 99%
“…The PLAY Tools (PLAYfun, PLAYparent, and PLAYself) have evidence of internal consistency (33), and PLAYself has acceptable test–retest reliability (30). There is initial evidence for the Pre-PLAY tool to assess physical literacy among preschool-aged children, but poor reliability among boys indicates a continued need for improvements (34). Among adults, previous studies have used the CAPL, PPLI, or composite measures to assess physical literacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, protecting children by equipping them with relevant motor skills, knowledge, and attitudes, necessary to face the dangers of drowning, while instilling the pleasure of moving in an aquatic environment, appears to be the major pedagogical challenge with regard to mitigating the tendencies towards a sedentary lifestyle in many young people [87].…”
Section: The Need For a Common Theoretical Framework And Tools To Pro...mentioning
confidence: 99%
“…11 Studies evaluating the PLAYfun constructs in children have found good inter-rater agreement (intraclass correlation coefficient [ICC] = 0.87). 25 Each task was assessed on a modified visual analog scale of 0 to 100, with a high score indicating increased competence. The rating system is divided into four general categories: initial (0 to 25), competent (26 to 50), emerging (51 to 75), and proficient (76 to 100).…”
Section: Instrumentation Physical Literacy Measuresmentioning
confidence: 99%